Standardised data collection for clinical follow-up and assessment of outcomes in differences of sex development (DSD): recommendations from the COST action DSDnet. Issue 5 (November 2019) - Flück, Christa; Nordenström, Anna; Ahmed, S Faisal; Ali, Salma R; Berra, Marta; Hall, Joanne; Köhler, Birgit; Pasterski, Vickie; Robeva, Ralitsa; Schweizer, Katinka; Springer, Alexander; Westerveld, Puck; et al.
Abstract : The treatment and care of individuals who have a difference of sex development (DSD) have been revised over the past two decades and new guidelines have been published. In order to study the impact of treatments and new forms of management in these rare and heterogeneous conditions, standardised assessment procedures across centres are needed. Diagnostic work-up and detailed genital phenotyping are crucial at first assessment. DSDs may affect general health, have associated features or lead to comorbidities which may only be observed through lifelong follow-up. The impact of medical treatments and surgical (non-) interventions warrants special attention in the context of critical review of current and future care. It is equally important to explore gender development early and refer to specialised services if needed. DSDs and the medical, psychological, cultural and familial ways of dealing with it may affect self-perception, self-esteem, and psychosexual function. Therefore, psychosocial support has become one of the cornerstones in the multidisciplinary management of DSD, but its impact remains to be assessed. Careful clinical evaluation and pooled data reporting in a global DSD registry will allow linking genetic, metabolomic, phenotypic and psychological data. For this purpose, our group of clinical experts and patient and parent representatives designed a template for structured longitudinal follow-up. In this paper, we explain the rationale behind the selection of the dataset. This tool provides guidance to professionals caring for individuals with a DSD and their families. At the same time, it collects the data needed for answering unsolved questions of patients, clinicians, and researchers. Ultimately, outcomes for defined subgroups of rare DSD conditions should be studied through large collaborative endeavours using a common protocol.